Fourier transform toolbox development - Ong, Hwee Yee. (2013)
In academic system, Fourier Transform was taught with limited visual aids, such as plotting of the graph in both domains, which can be complicated in visualizing. In order to simplify the understanding of Fourier Transform the right methodologies in teaching can be applied.